Factors Affecting the Incidence of Infertility - Rosdiana Rosdiana; Sukarni Setya Yuningsih (Global Health Science Group, 2023)
Infertility has become a global concern, not least in Indonesia, where the number continues to increase. Infertility will have a negative impact on society, especially in Indonesia, namely in addition to social and family problems that arise due to infertility, there is a problem that has become the main focus of several researchers in the world, namely decreased sexual satisfaction. The purpose of this study was to analyze the influence of age, body mass index, occupation, and menstrual cycle factors on the incidence of primary and secondary infertility. The design of this study is Case-Control. The location used for research in the working area of the Pabuaran Health Center from May to June 2023. The samples used for the case were 15 infertile pairs and 30 for control so that a total of 45 samples, the sampling technique used was total sampling. The multivariate analysis used in this study was multiple logistic regressions. Obesity increased the incidence of infertility up to 2 times and was statistically significant (aOR: 2.34; 95%CI 1.75 - 61.45; p value 0.010) and abnormal menstrual cycles increased the risk of infertile events by 1.8 times and were statistically significant (aOR: 1.85; 95%CI 0.95 - 42.25; p value 0.046).